Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Prerequisites - p.4 - Factoring Polynomials - Exercises - Page 39: 52



Work Step by Step

Use $-13x=-12x-x$ $12x^2-13x+1=12x^2-12x-x+1=(12x)x+(12x)(-1)+(-1)x+(-1)(-1)=12x(x-1)+(-1)(x-1)=(12x-1)(x-1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.